HYPOTHERMIA RATE IN PATIENTS UNDERGOING SURGERY PROGRAM AFTER SPINAL ANESTHESIA AT 115 PEOPLE HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Determination of hypothermia rate and related factors in elective surgery patients after spinal anesthesia.Subjects and methods: A cross-sectional descriptive study was conducted on 83 patients undergoing elective surgery at 115 People’s Hospital, from November 2024 to May 2025.Result: The rate of hypothermia in patients undergoing elective surgery after spinal anesthesia at 115 People’s Hospital was 47%. Factors related to hypothermia in patients undergoing elective surgery after spinal anesthesia at 115 People’s Hospital: female gender (p < 0.001); ASA II status or higher (p = 0.003); older age with the average age of the hypothermia group being 65.9 ± 13.5 years (p < 0.001); low body temperature before entering the operating room (p < 0.001); surgery time of 60 minutes or more (p = 0.025); type of lower limb surgery and urological surgery (p = 0.006).Conclusion: This study noted a high rate of hypothermia in elective surgery patients after spinal anesthesia, therefore body temperature should be routinely monitored in conscious patients, as well as increased continuing medical education training for anesthesiologists on the importance of temperature monitoring in patients undergoing regional anesthesia.
Keywords: Rate of hypothermia, perioperative hypothermia, spinal anesthesia.